Trends of two epidemic multidrug-resistant strains of Mycobacterium tuberculosis in Argentina disclosed by tailored molecular strategy - Monteserin, Johana (2019)
Two Mycobacterium tuberculosis strains-M (sublineage 4.1) and Ra (sublineage 4.3)-have long prevailed in Argentina among patients with multidrug-resistant tuberculosis (MDR-TB). Recently, budget constraints have hampered the surveillance of MDR-TB transmission. Based on whole-genome sequence analysis, we used M- and Ra-specific single nucleotide polymorphisms to tailor two multiplex allele-specific polymerase chain reactions (PCRs), which we applied to 252 stored isolates (95% of all newly diagnosed MDR-TB cases countrywide, 2015-2017). Compared with the latest data available (2007-2009), the M strain has receded (80/324 to 20/252, P < 0.0001), particularly among cross-border migrants (12/58 to 0/53, P = 0.0003) and HIV-infected people (30/97 to 7/74, P = 0.0007), but it still accounts for 4/12 new cases of extensively drug-resistant TB. Differently, the Ra strain remained stable in frequency (39/324 to 33/252) and contributed marginally to the extensive drug-resistance load (1/12). Our novel strategy disclosed recent trends of the two major MDR-TB strains, providing meaningful data to allocate control interventions more efficiently.